1999
DOI: 10.1135/cccc19990168
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zinc in Zn-Loaded ZSM-5 Zeolites in the Aromatization of n-Hexane

Abstract: Aromatization of n-hexane over zinc-modified ZSM-5 zeolites was investigated. It was shown that incorporation of zinc by ion exchange into cationic positions of NH4-ZSM-5 zeolite causes acid-site strength redistribution and generation of new relatively strong Lewis acid sites in zeolite increasing the selectivity of n-hexane aromatization in comparison with the parent NH4-ZSM-5 zeolite. Simultaneous presence of Lewis and Broensted acid sites in ZSM-5 zeolite does not affect the strength of Broensted acid sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…These results confirm our presumption 9 that ZnO as an extra-framework phase is an inactive component of the catalyst in the n-hexane aromatization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results confirm our presumption 9 that ZnO as an extra-framework phase is an inactive component of the catalyst in the n-hexane aromatization.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous work 9 it was shown that ZnO as an extra-framework phase is not able to activate n-hexane under given conditions (420°C). The presented activity/selectivity in the test reactions and TPDA data of thermally treated mechanical mixture ZnO + H-ZSM-5 are different from those of pure acid ZSM-5 zeolite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [15] the FT-IR measurements showed that in ion-exchanged ZnZSM-5/66 samples Zn species are located in cationic positions and represent relatively strong Lewis acid sites. FT-IR spectra of HZSM-5/70 and ZnZSM-5/70 samples are given in Figs ion-exchange by Zn.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of Zn is known to increase the selectivity to aromatics by providing an alternative path via dehydrogenation of the alkane [10]. Moreover, the presence of Zn species results in significant changes of the acidic properites of ZSM-5, reducing the Brönsted acid site density proportionally to the Zn loading, and generating new relatively strong Lewis acid sites [11,12].…”
Section: Introductionmentioning
confidence: 99%